Parental Abuse in the Jordanian Family: A Social Study in Al-Karak Governorate - Al-Bahri , Nasreen A. (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to identify the level of violence perpetrated by children toward their parents in Jordanian families. It also explores the degree of parental abuse in its different forms according to the variables of the parents’ gender, educational qualification, and income level. Methods: The study uses the analytical descriptive method. The study population consists of (73530) families from Al-Karak Governorate. The study sample consists of (2988) fathers and mothers; (1092) fathers and (1896) mothers were chosen by cluster random sampling. A questionnaire was distributed to the study sample after confirming its validity and reliability. Results: The results of the study show that the level of violence against parents in Al-Karak Governorate is moderate. The results also indicate that there are statistically significant differences in the level of violence against parents attributed to the gender variable (mothers are more abused) and to the educational qualification (parents with a bachelor degree, high school diploma, or less are more abused). There are also statistically significant differences attributed to the income level (parents with low income are more abused). Conclusion: The study recommends initiating religious guidance by specialists and holding media seminars on the need for respecting parents, especially mothers. It also invites for holding specialized seminars by psychologists for abused parents.